PENERAPAN MODEL PROJECT BASED LEARNING DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV UPTD SD NEGERI BERTINGKAT NAIKOTEN - fay, Melani margarita; koro, Maxsel; Nawa, Netty e. A. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study consists of several stages, namely planning, action implementation, observation, and reflection. The data analysis technique used in this study is descriptive qualitative by finding the completeness of student learning outcomes through observation sheets and tests with 32 research subjects consisting of 19 men and 17 women. This research was conducted at UPTD SD Negeri Naikoten with the results of the study showing that in cycle I of 32 students who completed, 10 students (51.25%) completed because they understood the material presented and did the test questions correctly. While those who did not complete were 22 students (68.75%) who did not complete because they did not pay attention to the teacher's explanation so they were unable to do the test questions given. The strengths and weaknesses of the teacher are that the teacher delivers the material clearly, the teacher gives students the opportunity to ask questions about the material presented and the teacher does not guide students to conclude the material. The strengths and weaknesses of the students are that the students pay attention to the teacher's explanation of the material and the students are unable to do the questions correctly. In cycle II, the learning outcomes of students increased from 32 students who completed, 31 students (96.87%) completed because they were active in learning, worked together with groups, understood the material presented and were able to do the test questions correctly. Based on the results of the study above, it can be concluded that the application of the project based learning model in science learning to improve the learning outcomes of grade IV students of UPTD SD Negeri Naikoten, can improve the learning outcomes of students.